Subarachnoid Hemorrhage Increases Level of Heme Oxygenase-1 and Biliverdin Reductase in the Choroid Plexus - Solár, Peter; Brázda, Václav; Levin, Shahaf; Zamani, Alemeh; Jančálek, Radim; Dubový, Petr; Joukal, Marek (Frontiers in Cellular Neuroscience, 2020)
Subarachnoid hemorrhage is a specific, life-threatening form of hemorrhagic stroke linked to high morbidity and mortality. It has been found that the choroid plexus of the brain ventricles forming the blood-cerebrospinal fluid barrier plays an important role in subarachnoid hemorrhage pathophysiology. Heme oxygenase-1 and biliverdin reductase are two of the key enzymes of the hemoglobin degradation cascade. Therefore, the aim of present study was to investigate changes in protein levels of heme oxygenase-1 and biliverdin reductase in the rat choroid plexus after experimentally subarachnoid hemorrhage induced by injection of non-heparinized autologous blood to the cisterna magna. Artificial cerebrospinal fluid of the same volume as autologous blood was injected to mimic increased intracranial pressure in control rats. Immunohistochemical and Western blot analyses were used to monitor changes in the of heme oxygenase-1 and biliverdin reductase levels in the rat choroid plexus after induction of subarachnoid hemorrhage or artificial cerebrospinal fluid application for 1, 3 and 7 days. We found increased levels of heme oxygenase-1 and biliverdin reductase protein in the choroid plexus over the entire period following subarachnoid hemorrhage induction. The level of heme oxygenase-1 was the highest early (1 and 3 days) after subarachnoid hemorrhage indicating its importance in hemoglobin degradation. Increased levels of heme oxygenase-1 were also observed in the choroid plexus epithelial cells at all time points after application of artificial cerebrospinal fluid. Biliverdin reductase protein was detected mainly in the choroid plexus epithelial cells, with levels gradually increasing during subarachnoid hemorrhage. Our results suggest that heme oxygenase-1 and biliverdin reductase are involved not only in hemoglobin degradation but probably also in protecting choroid plexus epithelial cells and the blood-cerebrospinal fluid barrier from the negative effects of subarachnoid hemorrhage.